Pelatihan Teknologi Tepat Guna Hydromodelling di SMK Perkapalan Hang Tuah Tanjung Uban Bintan untuk Mempersiapkan Kepribadian Unggul di Abad 21 - Mohd Ridho Baihaque; Adyk Marga Raharja; Firman Apriansyah; Deny Nusyirwan; Eko Prayetno; Anton Hekso Yunianto; Risandi Dwirama Putra (Jurnal Surya Masyarakat, 2024)
The suitability of technology can only be assessed in the context of the overall process of social and economic development. Means of assessment include technology assessment where one examines the broad impact of a technology, and socio-economic opportunity analysis where one starts from social needs and looks for technological solutions. The integration and balance of different levels of technology is as important as the selection of individual technologies. Superior Engineers in the 21st Century do not design for the community, but design with the community and enable design by the community. With the right training and education, engineers can help change communities for the better by equipping community members to meet their own needs and implement their own design responses. Higher Education Institutions are present in society and have a very big role in building the nation, Higher Education also occupies a strategic position in making changes in society through the function of transforming Human Resources (HR), Science and Technology (IPTEK) and social through the implementation of Tridharma activities which includes education, research and community service. With this background, the Raja Ali Haji Maritime University Maritime Engineering Study Program carries out Community Service in the form of Appropriate Technology (TTG) training in the form of ship model making training or known as Hydromodelling at the Hang Tuah Tanjung Uban Naval Vocational School, Bintan, Riau Islands. The training stages include introducing maritime insight and technology, explaining ship parts and then providing training related to ship design and production. The training has received a good response from the school and the students showed enthusiasm in carrying out each stage of the training.